Perilaku Pencarian Informasi Mahasiswa Fakultas Ekonomi Bisnis Islam Tahun 2019 di Perpustakaan UIN Sumatera Utara Medan - Ahmad Fauzi; Muhammad Rifky Fansuri; Naufal Akbar Halomoan; Yuda Aditia; Franindya Purwaningtyas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This essay discusses how students of the Faculty of Islamic Economics and Business use the State Islamic University of North Sumatra Medan Library in 2019 to find information. The following will be described in this paper: 1) Islamic Business Economics students' methods of information seeking at the Library of North Sumatra State Islamic University Medan; 2) the challenges that came up while trying to find information at the Medan North Sumatra State Islamic University Library; and, thirdly, the means by which these obstacles can be overcome. Data is gathered through questionnaires or surveys. It can be interpreted as follows on the basis of the findings of the research: ( 1) The Islamic Business Economics Department received positive feedback regarding the information-seeking behavior of students in 2019, as well as the obstacles these students encountered when looking for information. a) They do not require any information; b) Submissions must be incomplete; ( c) there is trouble in finding assortments since they are on an alternate rack from the OPAC framework; ( 3) There are ways to get around obstacles when looking for information: a) giving and finishing assortments as per the necessities of understudies and speakers; ( b) Create a collection shelf that is compatible with OPAC search engines to make it simple for users to locate the data they require. Keywords: Information search behavior; Information Needs, Librarians